Adaptation of muscle size and myofascial force transmission: a review and some new experimental results - Huijing, P. A.; Jaspers, R. T. (Scandinavian Journal of Medicine & Science in Sports, 2005)
This paper considers the literature and some new experimental results important for adaptation of muscle fiber cross-sectional area and serial sarcomere number. Two major points emerge: (1) general rules for the regulation of adaptation (for in vivo immobilization, low gravity conditions, synergist ablation, tenotomy and retinaculum trans-section experiments) cannot be derived. As a consequence, paradoxes are reported in the literature. Some paradoxes are resolved by considering the interaction between different levels of organization (e.g. muscle geometrical effects), but others cannot. (2) An inventory of signal transduction pathways affecting rates of muscle protein synthesis and/or degradation reveals controversy concerning the pathways and their relative contributions.